If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 10x = 58 + x Solving 4 + 10x = 58 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 4 + 10x + -1x = 58 + x + -1x Combine like terms: 10x + -1x = 9x 4 + 9x = 58 + x + -1x Combine like terms: x + -1x = 0 4 + 9x = 58 + 0 4 + 9x = 58 Add '-4' to each side of the equation. 4 + -4 + 9x = 58 + -4 Combine like terms: 4 + -4 = 0 0 + 9x = 58 + -4 9x = 58 + -4 Combine like terms: 58 + -4 = 54 9x = 54 Divide each side by '9'. x = 6 Simplifying x = 6
| 4x+30=6x+12 | | 16x^2-11x=0 | | -2(3-x)+2x=8 | | -7p-7p=3p+23 | | y=3x-2graph | | y=1.5x | | y=-2x+10 | | x(x-5)=14 | | 5x^2=10 | | 24x^2+52x+24=0 | | 8-3x=-12 | | a+25=9a+65 | | -3(6n+1)-2(7n-2)3(1n+5)=5(2n-1) | | x+38=8x+17 | | y=1.5*0.4 | | y=kx | | y+38=15y+10 | | -8p+6=44 | | 9r-5=22 | | 20y+5=85 | | -2n+7=1 | | 4x+5-2x=-2x+13 | | 4x+5-2x=-2+13 | | 0.7p+4.6=8.3-0.2p | | y+13y=56 | | 2x+3x+6x=12 | | y-5y=16 | | 2x-4x=9 | | 114=11c-(-26) | | 13x+4(5-2x)=3(x+12) | | 2y-4y=14 | | 8x+2y=10whatisy |